Non‐contrast‐enhanced abdominal MRA at 3 T using velocity‐selective pulse trains. Issue 3 (4th February 2020) - Zhu, Dan; Li, Wenbo; Liu, Dapeng; Liu, Guanshu; Pei, Yigang; Shin, Taehoon; Sedaghat, Farzad; Qin, Qin
Abstract : Purpose: Most existing non‐contrast‐enhanced methods for abdominal MR arteriography rely on a spatially selective inversion (SSI) pulse with a delay to null both static tissue and venous blood, and are limited to small spatial coverage due to the sensitivity to slow arterial inflow. Velocity‐selective inversion (VSI) based approach has been shown to preserve the arterial blood inside the imaging volume at 1.5 T. Recently, velocity‐selective saturation (VSS) pulse trains were applied to suppress the static tissue and have been combined with SSI pulses for cerebral MR arteriography at 3 T. The aim of this study is to construct an abdominal MRA protocol with large spatial coverage at 3 T using advanced velocity‐selective pulse trains. Methods: Multiple velocity‐selective MRA protocols with different sequence modules and 3D acquisition methods were evaluated. Sequences using VSS only as well as SSI+VSS and VSI+VSS preparations were then compared among a group of healthy young and middle‐aged volunteers. Using MRA without any preparations as reference, relative signal ratios and relative contrast ratios of different vascular segments were quantitatively analyzed. Results: Both SSI+VSS and VSI+VSS arteriograms achieved high artery‐to‐tissue and artery‐to‐vein relative contrast ratios above aortic bifurcation. The SSI+VSS sequence yielded lower signal at the bilateral iliac arteries than VSI+VSS, reflecting the benefit of the VSI preparation for imaging the distal branches. Conclusion: The feasibility of noncontrast 3D MR abdominal arteriography was demonstrated on healthy volunteers using a combination of VSS pulse trains and SSI or VSI pulse.